Next Generation Steering Device - Designing for Emergency Situation - Xie , Sylvia; Lin, Yuxin (My University, 2025)
As autonomous vehicles progress toward full automation, new challenges arise in ensuring safety during emergency scenarios where human intervention may still be necessary. This thesis, conducted in collaboration with Autoliv, investigates how Level 4 robotaxis can be designed to allow first responders to manually reposition stalled vehicles in critical situations. The project focuses on developing a fallback steering solution that addresses the absence of traditional controls in future vehicle interiors. Using a human-centered design process, including literature reviews, in-depth interviews with automotive experts and users, and iterative prototyping, the project identifies key user needs such as intuitive operation, mechanical reliability, and secure access. The result is HALOGRIP, a visible, analog steering device embedded within the dashboard of the robotaxi. Activated via a two-step ID verification process, the device uses a tilt-based mechanism for speed control and traditional rotation for steering. The system enables low-speed maneuvers without requiring training and supports quick response in space-constrained environments. Physical buttons and a HUD provide clear operational feedback, while mechanical locking ensures failsafe deployment. HALOGRIP offers a pragmatic and user-friendly solution that empowers emergency personnel without compromising the autonomy of the vehicle. Future work includes validating usability in real-world scenarios and refining integration across different vehicle platforms.
Keywords: Autonomous vehicles; Robotaxi; fallback control; emergency response; human-centered design; tilt-based interface; first responders